Dual Inhibitory Activity of Petroselinic Acid Enriched in Fennel Against Porphyromonas gingivalis - Yoshino, Nanami; Ikeda, Tsuyoshi; Nakao, Ryoma (Frontiers in Microbiology, 2022)
Increasing evidence has shown that a major periodontal pathobiont, Porphyromonas gingivalis, triggers oral dysbiosis leading to deterioration not only of periodontal health, but also of several systemic conditions. In the present study we identified remarkable anti-P. gingivalis activity of Foeniculum vulgare (fennel), an herbal plant used in Asian cuisine as well as in traditional medicine, by screening of 92 extracts prepared from 23 edible plants. The n-hexane-extracted fennel (HEF) showed a rapid lethal action toward P. gingivalis, while it was rather ineffective with a wide range of other oral commensal bacterial species. Morphological analysis using both high-speed atomic force microscopy and field emission scanning electron microscopy revealed that a low concentration of HEF (8 µg/mL) resulted in formation of protruding nanostructures composed of outer membrane vesicle (OMV)-like particles, while a high concentration of HEF (64 µg/mL) induced bacteriolysis with overproduction of OMVs with unusual surface properties. Interestingly, HEF treatment resulted in deprivation of two outer membrane transporter proteins, RagA and RagB, which is essential for nutrient acquisition in P. gingivalis, by extracellularly releasing RagA/RagB-enriched OMVs. Furthermore, HEF showed gingipain-inhibitory activity towards both arginine-specific (Rgps) and lysine-specific (Kgp) gingipains, resulting in blocking oral epithelial cell rounding and the subsequent detachment from culture dishes. Finally, we isolated petroselinic acid as a major bactericide as well as a gingipain inhibitor through a bioassay-guided fractionation of HEF. Taken together, our findings suggest clinical applicability of HEF and petroselinic acid for periodontitis therapy to eliminate P. gingivalis and its major virulence factors on the basis of the dual anti-P. gingivalis activity, i.e., rapid bacteriolysis and gingipain inhibition.